Purification and Properties of Polyphenol Oxidase of Dried Volvariella bombycina - Assemgul Sarsenova; Dudu Demir; Kardelen Çağlayan; Sardarbek Abiyev; Talshen Darbayeva; Cafer Eken (Biology, 2022)
Polyphenol oxidase (PPO) was purified and characterized from a dried wild edible and medicinal mushroom (V. bombycina). Using Sepharose 4B-L-tyrosine-p-aminobenzoic acid affinity chromatography, PPO was purified from the dried V. bombycina. The purification was completed with a 33.85-fold purification. On sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), the purified enzyme migrated as a single band. The molecular weight of the purified enzyme was estimated by SDS-PAGE to be about 25 kDa. Catechol, 4-methyl catechol, and pyrogallol were used as substrates to determine the enzyme activity and its kinetic parameters (Km and Vmax). At the optimum pH and temperature, dried V. bombycina PPO’s Km and Vmax values for catechol, 4-methyl catechol, and pyrogallol were found to be 1.67 mM–833.33 U/mL, 3.17 mM–158.73 U/mL, and 2.67 mM–3333.33 U/mL, respectively. Also investigated were the effects of pH and temperature on the enzymatic properties of PPO in dried V. bombycina. The optimum pH and temperature values for dried V. bombycina PPO obtained by using catechol, 4-methyl catechol, and pyrogallol as substrates were 6.5, 15 °C; 9.0, 20 °C; and 8.0, 15°C, respectively. This is the first study on the purification and characterization of PPO from dried V. bombycina.